Pretreatment of Vine Shoot Biomass by Choline Chloride-Based Deep Eutectic Solvents to Promote Biomass Fractionation and Enhance Sugar Production - Raquel Cañadas; Aleta Duque; Alberto Bahíllo; Raquel Iglesias; Paloma Manzanares (Bioengineering)
Vine shoots hold promise as a biomass source for fermentable sugars with efficient fractionation and conversion processes. The study explores vine shoots as a biomass source for fermentable sugars through pretreatment with two deep eutectic solvents mixtures: choline chloride:lactic acid 1:5 (ChCl:LA) and choline chloride:ethylene glycol 1:2 (ChCl:EG). Pretreatment conditions, such as temperature/time, solid/liquid ratio, and biomass particle size, were studied. Chemical composition, recovery yields, delignification extent, and carbohydrate conversion were evaluated, including the influence of washing solvents. Temperature and particle size notably affected hemicellulose and lignin dissolution, especially with ChCl:LA. Pretreatment yielded enriched cellulose substrates, with high carbohydrate conversion rates up to 75.2% for cellulose and 99.9% for xylan with ChCl:LA, and 54.6% for cellulose and 60.2% for xylan with ChCl:EG. A 50% acetone/water mixture increased the delignification ratios to 31.5%. The results underscore the potential of this pretreatment for vine shoot fractionation, particularly at 30% solid load, while acknowledging the need for further process enhancement.